EFFECT OF GUAVA LEAF (Psidium guajava), PAPAYA LEAF (Carica papaya) AND BETEL LEAF (Piper betle) EXTRACT ON THE ECTOPARASITE IN COMMON CARP (Cyrpinus carpio) - Hardhini, Rossy; Amir, Sadikin; Setyowati, Dewi Nuraeni (Jurnal Perikanan Unram, 2018)
Indonesia is a tropical country rich in biodiversity, including fish. Efforts to overcome the attacks of disease can be done through preventive action and treatment. Some chemicals commonly used by the farmers are not easy to decompose naturally, so categorized not environmentally friendly. Plants that have the potential to prevent disease are guava leaves with tannin content, betel leaf with essential oil content and papaya leaves with papain content. This research needs to be done to know the effect of immersion of guava leaf extract, betel and papaya on ectoparasit in carp fish. The study was conducted from July to August 2016 at the Aquaculture Laboratory, Study Program of Aquaculture, University of Mataram. This research was conducted using experimental method with Randomized Complete Design (RAL) Factorial with 2 factors, namely leaf type and concentration. Leaf type factor consists of guava leaf, betel leaf and papaya leaf, while the concentration factor consists of 0.0 g / l, 1.0 g / l and 1.5 g / l. Each treatment was repeated 3 times so it was obtained 27 experimental units. The data obtained in the research was analyzed using variance at 5% real level. The results showed that soaking carp fish using papaya leaf extract of 1.0 g / l can reduce the level of ectoparasitic attack on carp fish.